Pengaruh Pengawasan dan Beban Kerja Terhadap Kualitas Kerja Melalui Stres Kerja - Wahyu Agung Priyadi; Paulus Wardoyo; Wyatti Saddewisasi (Lembaga Pengembangan Kinerja Dosen, 2026)
The purpose of the research that has been carried out is to determine and analyze the effect of supervision and work load on work quality through work stress of employees of KPP Pratama Semarang Candisari. The research method used is SEM, with the technique of PLS. This study’s PLS-SEM analysis led to the following conclusions: 1) It is known that supervision and work load have a significant effect on work stress. While supervision has a negative influence on work stress, work load has a positive influence. 2) Supervision and work load both have significant and positive effect on work quality. 3) There is a significant effect of supervision and work load on work quality through work stress of employees at KPP Pratama Semarang Candisari. While significant effect of supervision on work quality through work stress has a negative influence, work load on work quality through work stress has positife effect..